Evaluation of material removal rate of stellite alloy using unconventional machining processes. (2021) - Rajasuthan, K.; Palpandi, M.; Gitanjali, Veernapati; Nithya, Panati; Subbiah, Ram; Marichamy, S.
Abstract: Stellite has consists cobalt-chromium alloys with complex carbides. It was a super alloy and it's specially designed for high wear and corrosion resistance. Due to its high strength and hardness, it was not processed through conventional machining techniques. The different unconventional machining techniques were considered for the evaluation of its machinability characteristics of stellite 1 alloy such as Abrasive Water Jet Machining (AWJM), Electrical Discharge Machining (EDM) and Laser Beam Machining (LBM) processes. Material Removal Rate (MRR) was compared and its influential parameters on MRR have been investigated through variance analysis. The different input factors were considered for the evaluation of MRR. The parametric effects and their correlation have been analyzed through interaction plots.